Financial integration in Latin America: a new strategy for a new normal - Enoch, Charles; Bossu, Wouter; Caceres, Carlos; Singh, Diva (Washington, D.C International Monetary Fund (IMF), 2017)
IMF page: "Many factors indicate that now may be the time for Latin American economies to work toward greater regional financial integration. Integration, with appropriate management of the risks, could bring needed diversification to Latin American financial sectors, and set the stage for further integration into the global economy as conditions permit. This book examines the financial landscapes of seven Latin American economies (LA-7): Brazil, Chile, Colombia, Mexico, Panama, Peru, and Uruguay, and makes a case for them to pursue regional financial integration. With growth slowing across much of the region resulting from the end of the commodity super-cycle and economic rebalancing in China, as well as fragmentation of the international banking system, policies to stimulate growth are needed. Chapters set out the benefits to the region of financial integration, the barriers to cross-border activity in banks, insurance companies, pension funds, and capital markets, as well as recommendations to address these barriers. Finally, the authors make the case that regional integration now could be a step toward global integration in the short term."
Foreword -- Preface -- Acknowledgements -- 1. Introduction / Charles Enoch -- 2. Benefits of more global and regional financial integration in Latin America / Luc Eyraud, Diva Singh, Bennett Sutton -- 3. Barriers to integration in banking / Iulia Ruxandra Teodoru -- 4. Barriers to integration in the insurance sector / Alla Myrvoda, Bennett Sutton -- 5. Barriers to integration for pension funds / Alla Myrvoda -- 6. Barriers to integration in capital markets / Alla Myrvoda, Bennett Sutton -- 7. Legal barriers to regional financial integration in Latin America / Laura Lorenzo, Wouter Bossu -- 8. Regional initiatives to achieve financial integration / Charles Enoch, Iulia Ruxandra Teodoru -- 9. Risks and mitigation for financial integration / Mohamed Afzal Norat, Carlos Caceres -- Appendix 1. Brazil -- Appendix 2. Chile -- Appendix 3. Colombia -- Appendix 4. Mexico: financial system overview -- Appendix 5. Panama -- Appendix 6. Peru -- Appendix 7. Uruguay -- Index.
Includes bibliographical references and index
Keywords: International economics; INTERNATIONAL ECONOMY; ECONOMIC INTEGRATION; INTERNATIONAL BANKING; LATIN AMERICA